2014
DOI: 10.4102/sajhrm.v12i1.648
|View full text |Cite
|
Sign up to set email alerts
|

Total rewards: A study of artisan attraction and retention within a South African context

Abstract: Orientation: The shortage of artisan skills remains a serious challenge in South Africa andis forcing employers to investigate which total reward factors contribute to the attractionand retention of this critical skills segment, as undifferentiated retention strategies are nolonger useful or even appropriate.Research purpose: The aim of this study was to further develop understanding of the total rewardfactors and the ideal combination and relative amount of total rewards that attract and retainartisans, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…This indicates that there was a high level of reliability for this model. The ratio of correctly predicted choices is called the hit rate, which is a common validity measure (Eggers et al, 2009;Schlechter et al, 2014). The hit rate for the conjoint model in this study was 38.5%, which means that the model was able to produce 38.5% correct predictions from the holdout set.…”
Section: Questionnaire 3: Choice-based Conjoint Task Questionnairementioning
confidence: 65%
See 3 more Smart Citations
“…This indicates that there was a high level of reliability for this model. The ratio of correctly predicted choices is called the hit rate, which is a common validity measure (Eggers et al, 2009;Schlechter et al, 2014). The hit rate for the conjoint model in this study was 38.5%, which means that the model was able to produce 38.5% correct predictions from the holdout set.…”
Section: Questionnaire 3: Choice-based Conjoint Task Questionnairementioning
confidence: 65%
“…generations, genders or race groups), has been the focus of research over the last few years (Codrington, 2008;Schlechter et al, 2014;Snelgar et al, 2013;Sutherland, 2004). Within the South African context, it has been found that specific reward strategies are related to the retention of Generation X, female employees and black professionals (Bussin & Toerien, 2015;Kotze & Roodt's, 2005;Krishnan, 2009;Masibigiri & Nienaber, 2011;Schlechter et al, 2014).…”
Section: Trends From the Research Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A study by Schlechter, Faught and Bussin (2014) provided a generic study in reward preferences of South African employees, and the results of this study showed that base pay was considered to be the most preferred reward component and an important reward component in attracting and retaining employees. This study notably also found differences between reward preferences and demographic variables, including age, gender and job level, providing support for segmentation of rewards based on certain demographic variables.…”
Section: Theoretical Framework Surrounding Rewardsmentioning
confidence: 99%